Oil and gas operations offshore [videorecording] : an introduction - The University of Texas at Austin. Petroleum Extension Service (Austin, TX : Petroleum Extension Service, University of Texas at Austin)
From whaling ships in the north Atlantic, which provided valuable lamp oil, to the offshore drilling rigs that produce petroleum by the barrelful, humans have long looked under the sea for sources of energy. But how does the oil and gas industry find the bounty underground? How are operations sustained on the often hostile open ocean? This video presentation tells the whole story of offshore exploration, drilling, production, and transportation. It provides descriptions of mobile offshore drilling units, life on an offshore rig, drilling techniques, and transportation to and from the rig